Translingual Writing: A Transformative Classroom Strategy in Multilingual Classroom of Nepal - Karki, Debraj (Tejganga Darpan, 2024)
Nepal is a linguistically and culturally diverse nation with 124 languages spoken by 142 ethnic nationalities (Central Bureau Statistics [CBS], 2021). Such diversity is the asset and beauty of a school classroom. The study aims at exploring the teachers’ and students’ experience of translingual writing in multilingual classroom in community school of Nepal. Similarly, it investigates the improvements and impacts of translingual writing in the community school of Nepal. The study has used a critical paradigm to interrogate the existing monolingual pedagogy in the multilingual classrooms. Exploratory Action Research (EAR) has been used as a research design to understand and improve classroom practices. The study has chosen a community school in Lalitpur district as the site of study. Focus group discussion, informal talks, and writing diaries are the tools of data collection. I have used translingual writing strategy with “my family theme” for the practices of writing skill. The study found that translingual writing has risen to substitute the existing conventional monolingual pedagogy. Similarly, the study found active participation when they are engaged in writing from their prior experiences of knowledge. The study has recommended considering translinguaging and plurilingual instruction as the main classroom tools to enhance English language proficiency.